2020
DOI: 10.1128/mbio.00719-20
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-Response Pathways Mediate Alkaline Survival in Diverse Fungi

Abstract: The ability for cells to maintain homeostasis in the presence of extracellular stress is essential for their survival. Stress adaptations are especially important for microbial pathogens to respond to rapidly changing conditions, such as those encountered during the transition from the environment to the infected host. Many fungal pathogens have acquired the ability to quickly adapt to changes in extracellular pH to promote their survival in the various microenvironments encountered during a host infection. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 99 publications
1
35
0
Order By: Relevance
“…In this mutant background, Rra1 is localized to endomembranes in both activating (pH 8) and inactivating conditions (pH 4) (Fig 4A and 4B). However, Rim signaling is still intact in the sre1 Δ mutant background as demonstrated previously by normal processing of the Rim101 transcription factor in response to elevated pH [26]. Together these data support that Rra1 membrane puncta are not essential for alkaline-induced Rim signaling.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In this mutant background, Rra1 is localized to endomembranes in both activating (pH 8) and inactivating conditions (pH 4) (Fig 4A and 4B). However, Rim signaling is still intact in the sre1 Δ mutant background as demonstrated previously by normal processing of the Rim101 transcription factor in response to elevated pH [26]. Together these data support that Rra1 membrane puncta are not essential for alkaline-induced Rim signaling.…”
Section: Resultssupporting
confidence: 84%
“…We previously identified a Rim-independent mechanism of the fungal alkaline pH response in which the Sre1 transcription factor and its downstream effectors in the ergosterol biosynthesis pathway are activated in response to alkaline pH [26]. Other work has also demonstrated that the sre1 Δ mutant has depleted levels of ergosterol in the plasma membrane and altered abundance of sterol-rich domains, affecting the localization of membrane-associated proteins [2729].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on C. neoformans helps us better understand this pathogen, contributes to the development of treatments for C. neoformans infections, and advances our understanding of fungal pathogens in general. RNA-Seq has been used extensively in C. neoformans studies to elucidate regulatory networks of protein-coding genes and mRNA structure and function ( Chang et al 2014 ; Chen et al 2014 ; Janbon et al 2014 ; Gish et al 2016 ; Chow et al 2017 ; Brown et al 2018 , 2020 ; Burke et al 2018 ; Wallace et al 2020 ; Yu et al 2020 ). While there is intense interest in the role of ncRNA in higher eukaryotes such as humans, relatively little work has explored the implications of ncRNA in fungi, with focus largely on model fungi such as Saccharomyces cerevisiae ( Bird et al 2006 ; Bumgarner et al 2009 , 2011 ; Gelfand et al 2011 ; Parker et al 2018 ) and Schizosaccharomyces pombe ( Ding et al 2012 ; Atkinson et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%